Dark current reduction in stacked-type CMOS-APS for charged particle imaging. - Takayanagi, I.
A stacked CMOS-active pixel sensor (APS) with a newly devised pixel structure for charged particle detection has been developed. At low operation temperatures (<200 K), the dark current of the CMOS-APS is determined by the hot carrier effect. A twin well CMOS pixel with a p-MOS readout and n-MOS reset circuit achieves low leakage current as low as 5×10-8 V/s at the pixel electrode under liquid nitrogen temperature of 77 K. The total read noise floor of 0.1 mVrms at the pixel electrode was obtained by nondestructive readout correlated double sampling (CDS) with the CDS interval of 21 s.
Keywords: 21 s; 77 to 200 K; Charged particle detection; Charged particle imaging; Dark current reduction; Fixed-pattern noise; Hot carrier effect; Leakage current; Low operation temperatures; Mass spectroscopy; n-MOS reset circuit; Nondestructive readout correlated double sampling; p-MOS readout; Pixel structure; Read noise; Stacked CMOS-active pixel sensor; Twin well CMOS pixel